Effects of lactic acid bacteria inoculants on the nutrient composition, fermentation quality, and microbial diversity of whole-plant soybean-corn mixed silage - Xu, Junzhao; Ma, Jianfei; Sa, Rula; Sui, Humujile; Wang, Xiaoni; Li, Qi; Zhu, Xinyue; Wu, Baiyila; Hu, Zongfu; Niu, Huaxin (Frontiers in Microbiology, 2024)
Few studies have investigated the changes in bacterial community succession in WPSCS inoculated with homofermentative and heterofermentative lactic acid bacteria (LAB) and whether WPSCS inoculated with LAB can improve fermentation quality by reducing nutrient losses. This study investigated the effect of Lactobacillus plantarum (L. plantarum)or Lactobacillus buchneri (L. buchneri) on the fermentation quality, aerobic stability, and bacterial community of WPSCS. A 40:60 ratio of whole-plant soybean corn was inoculated without (CK) or with L. plantarum (LP), L. buchneri (LB), and a mixture of LP and LB (LPB), and fermented for 14, 28, and 56 days, followed by 7 days of aerobic exposure. The 56-day silage results indicated that the dry matter content of the LP and LB groups reached 37.36% and 36.67%, respectively, which was much greater than that of the CK group (36.05%). The pH values of the LP, LB, and LPB groups were significantly lower than those of the CK group (P<0.05). The ammoniacal nitrogen content of LB was significantly lower than that of the other three groups (P<0.05), and the ammoniacal nitrogen content of LP and LPB was significantly lower than that of CK (P<0.05). The acetic acid content and aerobic stability of the LB group were significantly greater than those of the CK, LP, and LPB groups (P<0.05).High-throughput sequencing revealed a dominant bacteria shift from Proteobacteria in fresh forage to Firmicutes in silage at the phylum level. Lactobacillus remained the dominant genus in all silage.Linear discriminant analysis effect size (LEFSe) analysis identified Lactobacillus as relatively abundant in LP-treated silage and Weissella in LB-treated groups. The results of KEGG pathway analysis of the 16S rRNA gene of the silage microbial flora showed that the abundance of genes related to amino acid metabolism in the LP, LB, and LPB groups was lower than that in the CK group (P<0.05).In conclusion, LAB application can improve the fermentation quality and nutritional value of WPSCS 2 by regulating the succession of microbial communities and metabolic pathways during ensiling.Concurrently, the LB inoculant showed the potential to improve the aerobic stability of WPSCS.